KOMBINASI PROJECT BASED LEARNING DAN METODE EKSPERIMEN UNTUK MELATIHKAN KEMAMPUAN 5M - Sarah Miriam; Zainuddin Zainuddin (Vidya Karya, 2017)
Abstract. The education curriculum addressed the science learning which involves learner in the scientific process in order to find a product by promoting the scientific attitude. This idea has encouraged the researcher team to design an instructional which combines the project based learning model and the experiment method to train the 5M skills for students. The research subjects are the 6th semester students of physics education study program of the teacher training and educational sciences faculty of Lambung Mangkurat University (FKIP ULM) in the academic year of 2016/2017. The research used posttest only control group design. Learning effectiveness was gained from students’ project evaluation and posttest. The research result showed that students’ project was in good category with the mean score of 4.09. The students’ achievement has reached the individual mastery as big as 100%. It can be concluded that the combination of project based learning model and experiment method is effective to train the students’ 5M skills for the physics experiment course. Keywords: Project based learning, experiment method, 5M skills. Abstrak. Kurikulum pendidikan menghendaki pembelajaran sains yang melibatkan peserta didik dalam proses ilmiah untuk menemukan sebuah produk dengan mengedepankan sikap ilmiah. Hal ini mendorong tim peneliti untuk merancang pembelajaran yang mengkombinasikan project based learning dan metode eksperimen yang diharapkan mampu melatihkan  kemampuan 5M bagi mahasiswa. Subjek penelitian ini adalah mahasiswa semester 6 Pendidikan Fisika FKIP ULM pada tahun akademik 2016/2017. Desain penelitian menggunakan postest only control group design. Data efektivitas pembelajaran didapatkan dari evaluasi proyek mahasiswa dan postest. Hasil penelitian menunjukkan bahwa  proyek mahasiswa berkategori baik dengan skor rata-rata perolehan sebesar 4,09. Selanjutnya hasil belajar mahasiswa berhasil mencapai ketuntasan individu sebesar 100%. Dengan demikian dapat disimpulkan bahwa pembelajaran yang mengkombinasikan project based learning dan metode eksperimen efektif untuk melatihkan kemampuan 5M mahasiswa pada perkuliahan Eksperimen Fisika. Kata Kunci: Project based learning, metode eksperimen, kemampuan 5M.